Clinical and laboratory manifestations of childhood and adult-onset systemic lupus erythematosus in Cipto Mangunkusumo Hospital - Syarif Faisal; Arwin Akib; Taralan Tambunan (Indonesian Pediatric Society Publishing House, 2016)
Background Childhood-onset SLE is more severe than the adult type. Objective To compare the clinical and laboratory manifestations of childhood- and adult-onset systemic lupus erythematosus (SLE). Methods A retrospective study on child and adult SLE patients was conducted in the Division of Pediatric Allergy and Immunol- ogy, Department of Child Health and Department of Internal Medi- cine, Medical School, University of Indonesia/CiptoMangunkusumo Hospital (FKUI/RSCM) Jakarta. Subjects One hundred and twenty-nine subjects met the study criteria consisting on 54 childhood- onset (41.9%), 75 adult-onset (58.1%), and 122 (94.6%) females and 7 (5.4%) males from Janu- ary 1995 until December 2000. Results Fever, arthralgia and vasculitis were the most frequent signs found in both childhood-onset and adult-onset SLE. The liver, spleen, lymph nodes, cardiovascular, gastrointestinal tract, and eyes were the organs involved and significantly had a larger pro- portion in the childhood-onset. Decrease of C3 was more frequently found in the childhood-onset. Out of 17 childhood-onset patients who died, 13 died at the age of 0-11 year-old. Two of the adult- onset patients also died. Conclusion Childhood-onset SLE had some different character- istics compared to adult form